(untitled) (The International Journal of Educational Sciences and Arts, 2025)
Kingdom of Saudi Arabia in light of Vision 2030, examining its impact on resource efficiency and educational equity, and to propose a national framework for balanced and sustainable implementation. The study employed a qualitative approach using interviews, document analysis, and benchmarking with international experiences (Qatar, the United Kingdom, Japan, Malaysia, and the United States). The findings revealed that educational privatization enhances spending efficiency, diversifies funding sources, and improves the quality of educational services. However, it also raises challenges related to educational equity and equal opportunity. The study proposed a five-stage implementation model for effective privatization: Legislation, Experimentation, Generalization, Evaluation, and Development. It recommended establishing clear regulatory frameworks for public–private partnerships and strengthening monitoring and evaluation systems to ensure resource efficiency without compromising educational equity.